The Effect ABO Blood Groups On Severity Coronavirus Disease Clinical Symptoms (Albayan Scientific Journal, 2023)
Coronavirus disease 2019 is a new respiratory disease that spreads rapidly caused severe acute respiratory syndrome coronavirus-2 where the severity of symptoms varies from person to person according to different factors, including blood group type. In this study, we investigate the effect of different blood groups type ( A, B, AB, and O) on the different severity of clinical outcomes in COVID-19 patients and the risk of SARS-CoV-2 infection. with 100 patients from The initial monitoring and rapid response center for the Corona epidemic - Al-Bayda, were confirmed covid-19 positive by RT-PCR, the different clinical symptoms and blood groups type were questioned and investigated and we have used Analytic to statistics SPSS T.test, we absorption a relationship between the severity of symptoms with the different blood group A, B, AB, and O 48%, 13%, 3%, and 37%, respectively.
Keywords: ABO blood group; clinical outcome; COVID-19